Beach of Iracema: factors of stagnation of the static state of a coastal touristic site - Souza, Elsine Carneiro de (2007)
Leisure has become something that people really value nowadays and it's not just about having fun anymore. Based on that, one can perceive that the urge for traveling and the search for confort and pleasure outside their habitat has generated the strengthening of the tourism industry in the world. With that in mind, it's of paramount importance to realize that the tourism sector can be a tool that will produce collective profits provide that it's accomplishe in a sustainable way. As an example of a touristic site in which the relationship between the use and occupation have not become sustainable just like Praia de Iracema in Fortaleza. One can perceive that since the foundation of this area, the object evidenced two cycles of life, one in which it was valued and an other at times being degrading and at other times both processes taking place simultaneously, being static nowadays. Considering the social relevance of the object, this present work aims at understanding which factors contributed to the static state of a coastal touristic site. In order for that to happen, it was necessary the historical analysis of the phases experienced in that neighborhood through newspapers, magazines and photos sources, having bibliography related to the theme as supplement. Eventually, the author came to the conclusion that due to its attractiveness, Praia de Iracema was the target of real state speculation with he aid of tourism industry united haphazardly, causing the predatory exploitation of its space. In order for that reality to be modified, it is necessary to compreend that the value of touristic sites cannot be aimed at the economical aspect nevertheless it must stem from subjective values of each one.